A simultaneous strategy for the preparation of acetylation modified cellulose nanofiber/polypropylene composites. (1st February 2022) - Duan, Linjuan; Liu, Rongrong; Duan, Yan; Li, Zhiqiang; Li, Qun
Abstract: In this study, a simultaneous method with nano-fibrillation of acetylation modified fibers (A-cellulose) and preparation of cellulose nanofiber (CNF)/apolar polymer composites are proposed. The A-cellulose and isotactic polypropylene (iPP) were initially mixed and then melt-compounding in a twin-screw extruder. Due to the reduction of hydrogen bonding force inside A-cellulose and the high shear force provided by the extruder, acetylated cellulose nanofiber (A-CNF) distributed with the state of a three-dimensional network in PP composites (ACPP) were successful prepared. The scanning electron microscopy (SEM) images of A-CNF, dynamic mechanical analysis (DMA) and X-ray diffraction (XRD) results of ACPP showed that the A-CNF had good interface compatibility with PP matrix, and had the effects of inducing PP crystallization, decreasing crystal size and increasing the ratio of γ crystals in composites, which could improve the mechanical and thermodynamic properties of composites.